Feeding Pattern and Nutritional Status of Under Two Years of Children in Climate-vulnerable Southern Barisal and Khulna Region of Bangladesh (Bangladesh Journal of Nutrition, 2020)
Globally, undernutrition is responsible for almost half of all infant deaths. Recommended infant and young child feeding (IYCF) practices have been considered to be protective against undernutrition. The objective of the study was to assess the pattern of IYCF practices as well as the nutritional status of children 0-23 months in Barishal and Khulna region of Bangladesh. To assess the current feeding practices and factors associated with nutritional status, the present study used secondary data from a baseline survey of the project titled, "Integrated Agriculture and Health-based Interventions for Improved Food and Nutrition Security in Selected Districts of Southern Bangladesh". Socio-demographic, anthropometric and IYCF indicators were analyzed. The results showed that 30.6% of children met minimum dietary diversity (MDD) whereas 76.2% of children attained minimum meal frequency (MMF) and 29.1% of children had minimum acceptable diet (MAD) subsequently. The prevalence of stunting, wasting and underweight was 27.1%, 8.9%and 20.1%, respectively. All indicators of the IYCF were significantly associated with age and MAD was statistically significant with the children's household wealth index and sex. There was a high prevalence of underweight among children who did not receive MDD (25.4%), MMF (26.5%), or (MAD) (25.3%), compared to children who received MDD (20.6%), MMF (22.9%), or MAD (20%). In comparison with national data, IYCF practices in Barishal districts are better than those in Khulna districts, but still fall below the national target of 34% by 2025. Therefore, to optimize the IYCF practices among the children extensive programmes and research work are required.Bangladesh J. Nutr. Vol. 33, December 2020, P: 73-85